2002
DOI: 10.1113/jphysiol.2001.015644
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent variations in the directional sensitivity of balance corrections and compensatory arm movements in man

Abstract: We investigated the effects of ageing on balance corrections induced by sudden stance perturbations in different directions. Effects were examined in biomechanical and electromyographic (EMG) recordings from a total of 36 healthy subjects divided equally into three age groups (20-34, 35-55 and 60-75 years old). Perturbations consisted of six combinations of support-surface roll (laterally) and pitch (forward-backward) each with 7.5 deg amplitude (2 pure pitch, and 4 roll and pitch) delivered randomly. To reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
203
4
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(233 citation statements)
references
References 85 publications
12
203
4
7
Order By: Relevance
“…Recently, however, this concept has been challenged for motion occurring during quiet stance (Aramaki et al 2001;Loram and Lakie 2002). Indeed, as body motion increases in amplitude and direction from that of quiet standing (Fitzpatrick et al 1992(Fitzpatrick et al , 1994Winter et al 1996Winter et al , 1998Gatev et al 1999;Accorneo et al 1997), to that induced by a support surface perturbation in the pitch plane alone (Cordo and Nashner 1982;Allum et al 1993;Horak et al 1997), and finally to that induced by combined roll and pitch plane perturbations (Moore et al 1988;Maki et al 1994aMaki et al , 1994bHenry et al 1998b;Carpenter et al 1999;Allum et al 2002), the multi-link nature of human postural corrections becomes increasingly prominent. This multi-link strategy involves hinging at the knees, hips and lower vertebral column, in addition to ankle joint motion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, this concept has been challenged for motion occurring during quiet stance (Aramaki et al 2001;Loram and Lakie 2002). Indeed, as body motion increases in amplitude and direction from that of quiet standing (Fitzpatrick et al 1992(Fitzpatrick et al , 1994Winter et al 1996Winter et al , 1998Gatev et al 1999;Accorneo et al 1997), to that induced by a support surface perturbation in the pitch plane alone (Cordo and Nashner 1982;Allum et al 1993;Horak et al 1997), and finally to that induced by combined roll and pitch plane perturbations (Moore et al 1988;Maki et al 1994aMaki et al , 1994bHenry et al 1998b;Carpenter et al 1999;Allum et al 2002), the multi-link nature of human postural corrections becomes increasingly prominent. This multi-link strategy involves hinging at the knees, hips and lower vertebral column, in addition to ankle joint motion .…”
Section: Introductionmentioning
confidence: 99%
“…Our second goal was to clarify the pathophysiology of trunk stiffness which we suggested helps cause impaired balance control with ageing and in neurological disorders, including Parkinson's disease and severe proprioceptive loss (Carpenter et al 2004;Allum et al 2002;Bloem et al 2002). In all these groups, changes in trunk roll motion were noted as early as 50 ms after a postural perturbation, suggesting that active stiffening prior to the perturbationrather than inappropriate active postural reactions-was mainly responsible for the loss of trunk flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, studies of balance-recovery reactions have tended to focus primarily on the lower limbs; however, there is an increasing awareness that rapid movements of the upper limbs also play an important role in stabilizing the body, both in daily life McIlroy 1996, 1997;Rabinovitch et al 2009) and in experimental settings (Romick-Allen and Schultz 1988;McIlroy and Maki 1995b;Maki and McIlroy 1997;Tang et al 1998;Allum et al 2002;Marigold and Patla 2002;Marigold et al 2003;Misiaszek 2003;Cham and Sandrian 2007;Roos et al 2008;Pijnappels et al 2010). In the event that attempts to recover balance are unsuccessful, arm reactions may also act to help absorb the energy of the fall and protect against head injury (Roberts 1978) or hip fracture (Feldman and Robinovitch 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even small balance perturbations can evoke arm reactions, particularly when the perturbation is novel or unexpected (Maki and Whitelaw 1993;Corbeil et al 2004), and it has been proposed that the arm movements can help to stabilize the body through various 'counter-balancing' inertial or gravitational mechanisms (Romick-Allen and Schultz 1988; Allum et al 2002;Marigold and Patla 2002;Marigold et al 2003;Misiaszek 2003;Hoff 2007;Marigold and Misiaszek 2009;Roos et al 2008;Pijnappels et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that ageing-related deterioration undermines daily life activities of older adults in different aspects. Older adults are more vulnerable than young adults with decreased visuospatial working memory [1,2], deteriorated cognitive processes [3,4], increased movement variability and instability [5], decreased directional sensitivity of balance [6] and decreased muscle strength [7]. Ageing creates differences in neural control of movement within different brain regions, such as the prefrontal cortex and basal ganglia, which in turn affects motor performance [8].…”
Section: Introductionmentioning
confidence: 99%